南极高纬度沿岸海域的细菌生产力 - 彭安国; 黄奕普; 邱雨生; 陈敏; 刘广山 (厦门大学, 2005)
中国第18次南极科学考察期间,采用3H 胸腺嘧啶核苷示踪法测定了普里兹湾及邻近海区的细菌生产力,并对细菌生产力的水平、垂直分布及细菌生产力与相关要素之间的相互关系进行了研究和讨论.结果表明:该研究海域细菌生产力的变化范围为1.51~21.7 ngC·dm-3·h-1,平均为7.77 ngC·dm-3·h-1.细菌生产力空间分布特征:水平呈非均匀分布,东、南、西3面较高,北、中部较低,而垂直分布则有3种类型,即次表层极大值型、随深度递增型和极大极小叠加型.细菌生产力随培养时间的延长而增大,到一定时间后趋于最大值;细菌生产力昼夜变化的结果表明光照强度和水温对细菌生产力的测值有重要的影响. 【英文摘要】 During the 18th Chinese National Antarctic Research Expeditions (CHINARE),the way using (~3H)-thymidine nucleoside as a tracer to determine bacterial production in the high latitude coastal waters-the Prydz Bay and its adjacent sea area was used.The spatial distribution features of bacterial production and the factors affecting the bacterial production were studied and discussed.The calculated results showed that the bacterial production varied in the range of (1.51~21.7)·ngC·dm~(-3)·h~(-1),with an average . 国家自然科学基金(49836010);“十五”南极公益项目(2001DIA 50040)资助